Automated Recognitions of White Blood Cells - Bajirao, More Kaveri (Journal of Advanced Research in Information Technology, Systems and Management; Vol 3 No 2 (2019): Journal of Advanced Research in Information Technology, Systems & Management, 2021)
Healthcare services are important part of   cities. Now a day’s healthcare plays important role in the transformation of cities into smart cities. Leucocytes play a vital role in immune system which helps to protect the body against both infectious disease and foreign invaders. Identification of leukocytes in blood smear provides important information to pathologist as well as doctors to analyze and predicts different types of hematic diseases, such as AIDS and blood cancer (Leukemia). Most of the time, the health professional are interested on leucocytes in white blood cells only. Digital image processing procedures can help them in their examine and detecting. For example, disease like cancer and AIDS is detected based on the total count of the WBC in the human body. In the proposed framework, leucocyte is first segmented into two dominant elements, nucleus and cytoplasm, followed by extraction of features. The identification of leucocytes can be done with the help of adoptive gradient vector flow snake algorithm. How to cite this article: Bajirao MK, Bhaskar SD, Dnyneshwar KK. Automated Recognitions of White Blood Cells. J Adv Res Info Tech Sys Mgmt 2019; 3(2): 4-6